Corrosion-resistant cobalt phosphide electrocatalysts for salinity tolerance hydrogen evolution - Xu, Xinwu; Lu, Yang; Shi, Junqin; Hao, Xiaoyu; Ma, Zelin; Yang, Ke; Zhang, Tianyi; Li, Chan; Zhang, Dina; Huang, Xiaolei; He, Yibo (Nature communications, 2023)
Seawater electrolysis is a viable method for producing hydrogen on a large scale and low-cost. However, the catalyst activity during the seawater splitting process will dramatically degrade as salt concentrations increasing. Herein, CoP is discovered that could reject chloride ions far from catalyst in electrolyte based on molecular dynamic simulation. Thus, a binder-free electrode is designed and constructed by in-situ growth of homogeneous CoP on rGO nanosheets wrapped around the surface of Ti fiber felt for seawater splitting. As expected, the as-obtained CoP/rGO@Ti electrode exhibits good catalytic activity and stability in alkaline electrolyte. Especially, benefitting from the highly effective repulsive Cl − intrinsic characteristic of CoP, the catalyst maintains good catalytic performance with saturated salt concentration, and the overpotential increasing is less than 28 mV at 10 mA cm −2 from 0 M to saturated NaCl in electrolyte. Furthermore, the catalyst for seawater splitting performs superior corrosion-resistance with a low solubility of 0.04%. This work sheds fresh light into the development of efficient HER catalysts for salinity tolerance hydrogen evolution. Seawater electrolysis for hydrogen production is limited by the poor salinity tolerance of catalysts. CoP was found to repel chlorine while attracting H2O molecules to form a thin layer on the catalyst surface, thus constructing a corrosion-resistant CoP/rGO@Ti catalyst for seawater splitting.